Development of Machine Learning Algorithms for Prediction of 30‐Day Mortality After Surgery for Spinal Metastasis. Issue 1 (July 2019) - Karhade, Aditya V; Thio, Quirina C B S; Ogink, Paul T; Shah, Akash A; Bono, Christopher M; Oh, Kevin S; Saylor, Phil J; Schoenfeld, Andrew J; Shin, John H; Harris, Mitchel B; Schwab, Joseph H
Abstract : BACKGROUND: : Preoperative prognostication of short‐term postoperative mortality in patients with spinal metastatic disease can improve shared decision making around end‐of‐life care. OBJECTIVE: : To (1) develop machine learning algorithms for prediction of short‐term mortality and (2) deploy these models in an open access web application. METHODS: : The American College of Surgeons, National Surgical Quality Improvement Program was used to identify patients that underwent operative intervention for metastatic disease. Four machine learning algorithms were developed, and the algorithm with the best performance across discrimination, calibration, and overall performance was integrated into an open access web application. RESULTS: : The 30‐d mortality for the 1790 patients undergoing surgery for spinal metastatic disease was 8.49%. Preoperative factors used for prognostication were albumin, functional status, white blood cell count, hematocrit, alkaline phosphatase, spinal location (cervical, thoracic, lumbosacral), and severity of comorbid systemic disease (American Society of Anesthesiologist Class). In this population, machine learning algorithms developed to predict 30‐d mortality performed well on discrimination (c‐statistic), calibration (assessed by calibration slope and intercept), Brier score, and decision analysis. An open access web application was developed for the best performing model and this web application can be found here: https://sorg‐apps.shinyapps.io/spinemets/ . CONCLUSION: : Machine learning algorithms are promising for prediction of postoperative outcomes in spinal oncology and these algorithms can be integrated into clinically useful decision tools. As the volume of data in oncology continues to grow, creation of learning systems and deployment of these systems as accessible tools may significantly enhance prognostication and management.